Analysis of Adhesion Strength and Surface Hardness of 6061 Aluminum Alloy Resulting from Powder Coating with Variations in Sandblasting Process Time - Hasugian, Panca Putra; Salahudin, Xander; Mulyaningsih, Nani (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
The success of powder coating is highly dependent on specimen preparation, one of which is sandblasting. This study aims to analyze the effect of variations in sandblasting time on surface roughness, adhesion strength, and surface hardness of powder coated 6061 aluminum alloy. The research method used was quantitative experimental. Specimens measuring 50 mm × 50 mm × 3 mm were sandblasted with time variations of 15 seconds, 35 seconds, and 55 seconds, and their surface roughness was measured. Furthermore, the specimens that have undergone the sandblasting process will be continued for the powder coating process and tested for adhesion strength and surface hardness. The results showed that the highest roughness, adhesion strength, and surface hardness were found in the 55-second variation with a roughness value of 6.18 µm, an adhesion strength value of 5.63 MPa, and a surface hardness value of 14.45 VHN. This shows that the longer the sandblasting time, the higher the surface roughness, the higher the adhesion strength and the surface hardness.The success of powder coating is highly dependent on specimen preparation, one of which is sandblasting. This study aims to analyze the effect of variations in sandblasting time on surface roughness, adhesion strength, and surface hardness of powder coated 6061 aluminum alloy. The research method used was quantitative experimental. Specimens measuring 50 mm × 50 mm × 3 mm were sandblasted with time variations of 15 seconds, 35 seconds, and 55 seconds, and their surface roughness was measured. Furthermore, the specimens that have undergone the sandblasting process will be continued for the powder coating process and tested for adhesion strength and surface hardness. The results showed that the highest roughness, adhesion strength, and surface hardness were found in the 55-second variation with a roughness value of 6.18 µm, an adhesion strength value of 5.63 MPa, and a surface hardness value of 14.45 VHN. This shows that the longer the sandblasting time, the higher the surface roughness, the higher the adhesion strength and the surface hardness.